Perbandingan Kebijakan Ketenagakerjaan Indonesia dan Australia dalam Pengurangan Pengangguran - Vina Terina Dea Anggita; Arif Zainudin; Agus Setio Widodo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze and compare labor market policies in Indonesia and Australia in their efforts to reduce unemployment. Unemployment is understood as a structural issue influenced by labor market conditions, the quality of human resources, and the institutional capacity of the state. This research employs a qualitative method with a comparative public policy approach. Data are collected through a literature review and document analysis of regulations, official government reports, and relevant academic publications related to labor policies in both countries. The analysis is conducted using a descriptive-comparative method by examining labor market policies, vocational training systems, labor market information systems, and social protection measures. The findings indicate that Australia has more effective and adaptive labor policies, supported by strong institutional capacity, an integrated labor market data system, and active labor market policies that are responsive to economic changes. In contrast, Indonesia continues to face significant challenges, including the dominance of the informal sector, skills mismatches within the workforce, and weak coordination and implementation of labor policies. The study concludes that strengthening cross-sectoral collaboration, developing a comprehensive labor market information system, and expanding active labor market policies are key strategies to improving the effectiveness of labor policies in Indonesia.